2015
DOI: 10.7860/jcdr/2015/12825.6249
|View full text |Cite
|
Sign up to set email alerts
|

Cervicofacial Actinomycosis Mimicking Osseous Neoplasm: A Rare Case

Abstract: A 13-year-old male child reported to the Department of Oral and Maxillofacial Pathology with the chief complaint of pain and difficulty in opening the mouth for last 6-7 months. Initially there was a small painful nodule over the right infra auricular region which gradually increased in size to attain the present dimensions. The patient did not give any history of trauma or tooth extraction. Many local physicians and dental surgeons were consulted and the patient received several courses of antibiotics and ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 3 publications
0
13
0
4
Order By: Relevance
“…The word Actinomycosis comes from the Greeks where “aktino” refers to the radiating appearance of sulphur granules and “mykos” refers to mycelia relating to a fungal disease. It is a rare infectious disease in humans but much more common in animals such as cattle, horses, pigs, and dogs [ 11 ]. In 1845, Von Langenbeck reported the first case in humans and attributed it to a fungus.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The word Actinomycosis comes from the Greeks where “aktino” refers to the radiating appearance of sulphur granules and “mykos” refers to mycelia relating to a fungal disease. It is a rare infectious disease in humans but much more common in animals such as cattle, horses, pigs, and dogs [ 11 ]. In 1845, Von Langenbeck reported the first case in humans and attributed it to a fungus.…”
Section: Discussionmentioning
confidence: 99%
“…In 1845, Von Langenbeck reported the first case in humans and attributed it to a fungus. In 1891, Israel and Wolff first isolated the microorganism from humans and Waksman showed that Actinomyces is a gram-positive bacterium; not a fungus in the 1960s [ 11 , 12 ]. Over 30 species have been identified, of which the most common microorganism causing infections in humans is A. israelii , and to a lesser extent A. naeslundii , A. meyeri , A. odontolyticus , A. viscosus , A. propionica , and A. gerencseriae [ 2 , 9 , 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations